Epictetusian Rationality - Gregory Ponthiere (Global Labor Organization (GLO), 2022)
According to Epictetus, mental freedom and happiness can be achieved by distinguishing between, on the one hand, things that are upon our con- trol (our acts, opinions and desires), and, on the other hand, things that are not upon our control (our body, property, offi ces and reputation), and by wishing for nothing that is outside our control. This article proposes two accounts of Epictetus's precept: the I account of Epictetus's precept requires indifference between outcomes differing only on circumstances, whereas the IB account requires indifference between outcomes involving the best replies to circumstances. We study the implications of these precepts on the preference relation and on the existence of Epictetusian rationality. The I account implies that the preference relation satisfies in- dependence of circumstances, whereas the IB account implies robustness to dominated alternatives. Unlike the IB account, the I account rules out (counter)adaptive preferences. Finally, when examining game-theoretical implications of Epictetusian rationality, we show that the two accounts of Epictetus's precept exclude the existence of prisoner's dilemmas.
Keywords: B11; D01; D10; 330; rationality; Epictetus; preferences; indifference; independence; adaptive preferences